2007
DOI: 10.1007/s11284-006-0321-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil and vegetation nutrient response to bison carcasses in Białowieża Primeval Forest, Poland

Abstract: Ungulate carcasses can have important effects on the surrounding soil and vegetation. The impact of six carcasses of European bison (Bison bonasus) was investigated for the first time in a natural temperate forest (Białowie_ za, Poland) by measuring soil and plant nutrient concentrations along a gradient extending from the centre of each carcass. Calcium concentration and pH were found to be higher at the centre of the carcass, decreasing towards the periphery. This effect lasted up to 7 years after the death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 16 publications
2
65
2
Order By: Relevance
“…For forensic purposes it shall be highly interesting to look at the testate amoeba community and at what time the population recovers totally and whether this follows a succession pattern. As nutrient levels can remain high up to several years in soil influenced by cadavers [60][61][62], the influence of long-gone cadavers on soil communities can also be expected to remain visible for over one year, as indeed suggested by our results. Longer-term experiments are required to study in further detail the re-colonisation patterns (which species re-colonise first, how do these patterns relate to food sources such as bacteria, fungi, other protists, etc.)…”
Section: Effect Of Decomposing Pigs On Soil Testate Amoebaesupporting
confidence: 79%
“…For forensic purposes it shall be highly interesting to look at the testate amoeba community and at what time the population recovers totally and whether this follows a succession pattern. As nutrient levels can remain high up to several years in soil influenced by cadavers [60][61][62], the influence of long-gone cadavers on soil communities can also be expected to remain visible for over one year, as indeed suggested by our results. Longer-term experiments are required to study in further detail the re-colonisation patterns (which species re-colonise first, how do these patterns relate to food sources such as bacteria, fungi, other protists, etc.)…”
Section: Effect Of Decomposing Pigs On Soil Testate Amoebaesupporting
confidence: 79%
“…cicada carcasses [33]). Previous studies of ungulate carcass effects on soil and vegetation have been conducted only in temperate or arctic environments [17][18][19]34], and Towne [17] suggested that abundant scavenger communities would reduce the nutrient effect of carcasses in tropical systems. In our subtropical system, however, we found that carcasses created clear and biologically significant effects on soil P, N and rspb.royalsocietypublishing.org Proc.…”
Section: Discussionmentioning
confidence: 99%
“…Animal carcasses are important biotic agents that create localized nutrient pulses while at the same time aggregating parasites in the environment. Carcasses can create nutrient hotspots that can persist for several years, altering soil fertility and vegetation response [17][18][19]. However, it has yet to be determined how herbivores respond to these hotspots, including whether lingering visual or olfactory cues from a carcass serve as a deterrent to herbivores or if these nutrient-rich sites eventually become preferred foraging locations.…”
Section: Introductionmentioning
confidence: 99%
“…5.1). This increase in soil nutrient concentration in the vicinity of a carcass shows a gradient decreasing towards the periphery and which may persist for several years (Towne 2000;Danell et al 2002;Melis et al 2007). For vegetation, the changes are more drastic and can occur both in terms of biomass and community structure.…”
Section: The Role Of Carcasses Within Ecosystemsmentioning
confidence: 98%
“…From an abiotic point of view, it is noteworthy that the appearance of a carcass represents a key natural "disturbance" in the composition of soils and plant communities, because it means a sudden availability of nutrients (Towne 2000;Melis et al 2007). In fact, based on the high levels recorded of soil nutrients deposit, biomass production and activity of edaphic fauna, the experts have defined the carcasses as "islands of decomposition" (Carter et al 2007;Selva and Cortés-Avizanda 2009;Fig.…”
Section: The Role Of Carcasses Within Ecosystemsmentioning
confidence: 99%